2010
DOI: 10.1007/s10750-010-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterioplankton in the littoral and pelagic zones of subtropical shallow lakes

Abstract: We measured bacterioplankton (phylotypes detected by fluorescent in situ hybridisation, morphometric forms, abundance and production) in samples collected in summer in the littoral and pelagic zones of 10 subtropical shallow lakes of contrasting area (from 13 to 80,800 ha). Compared to the pelagic zones, the littoral zones were overall characterised by higher macrophyte dominance and lower concentrations of total phosphorus and alkalinity and higher concentrations of dissolved organic carbon (DOC) and humic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…The importance of biotic variables in structuring freshwater bacterioplankton communities has been shown before (e.g. Wu et al, 2007;Ng et al, 2010) and densities of antagonists including lytic bacterial viruses, bacterivorous protists and zooplankton (e.g. Allgaier and Grossart, 2006;Niu et al, 2011), macrophyte abundance (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…The importance of biotic variables in structuring freshwater bacterioplankton communities has been shown before (e.g. Wu et al, 2007;Ng et al, 2010) and densities of antagonists including lytic bacterial viruses, bacterivorous protists and zooplankton (e.g. Allgaier and Grossart, 2006;Niu et al, 2011), macrophyte abundance (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…UV exposure of macrophytes products of degradation in Lake Mangueira has been demonstrated to decrease bacterial production, possibly by formation of H 2 O 2 (They et al, submitted). The release of allelopathic substances by (mainly submersed) macrophytes is widely known (Gross et al, 2007; Mulderij et al, 2007), and has been considered as a possible explanation for lower bacterial diversity (Wu et al, 2007) and metabolism (They et al, 2010) in areas extensively colonized by macrophytes. We have data on Fe and silicate from the extensive campaigns that were not included in the results because they are out of objectives of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rooney and Kalff (2003) surveyed nine lakes with different percentages of macrophyte coverage, and found a significant decrease in the bacterial respiration rate with increasing macrophyte coverage. In southern Brazil, bacterial metabolism and biovolume were found to be lower in the littoral (covered with macrophytes) than in the pelagic zones of subtropical shallow lakes (They et al, 2010). If bacterial metabolism can be lower in the presence of macrophytes, there is a contradiction with the common belief that macrophyte-derived carbon always benefit bacteria, and it is reasonable to hypothesize that carbon cycling can be affected in the littoral zones of lakes that are extensively colonized by these plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, macrophytes provide a source of increased supply of organic matter in the littoral zone (Kominkova et al 2000; Wu et al 2010, Obolewski et al 2011). The presence of water plants is positively correlated with the amount and the biomass of microorganisms, which also affects their biodiversity (Wu et al 2010; Ng et al 2010). It has been reported that on the reed Phragmites australis alone, >600 species of fungi can be isolated (Gessner and van Ryckegem 2003; Wu et al 2010).…”
Section: Discussionmentioning
confidence: 99%